(3EYQGH GdbQBf GdcQjes
(3ChdgG (B:s
(3Chd GdehLhO ajg CKfGA EYQGH bhdg JYGdi (B( (3Hd YLHJ hSNQhf (B) (3ef ShQI GdUGaGJ hChd GdehLhO efg Udi Gddg Ydjg hSde Ydi EVeGQ Gdbhd Ci bd Ch bGd Hd YLHJ s
(3BNQgG (B:s
(3jfJgi CKfGA EYQGH ShQI GdMGbI hBNQ eG ajg bhdg Ke GdLMje Udhg GdLMje eaYhd KGfi ddJUdjI hcaGc OdjdkG aSha fUdjg s
(3ai CKfGA GdfSNI HJQ YfO ShQg GdUas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJaSjQ hYdhe GdbQBfs